2005
DOI: 10.2527/2005.831243x
|View full text |Cite
|
Sign up to set email alerts
|

Diet modifications to improve finishing pig growth performance and pork quality attributes during periods of heat stress1,2

Abstract: A total of 196 barrows (88 kg) were used in a 2 x 2 factorial arrangement of treatments and housed in a facility (seven pigs per pen) where temperatures cycled between 27 and 35 degrees C. Treatments consisted of (as-fed basis) two CP levels (13.6 or 11.3%) and two levels of added fat (1 or 8%). Diets were formulated to the same true digestible lysine:ME ratio (1.68 g of lysine/Mcal of ME). Diets were fed and growth variables were measured until pigs reached 114 kg of BW. Ham and LM (loin) 24-h pH (PH24), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 23 publications
9
33
0
Order By: Relevance
“…In the present study, effect of crude protein only occurred (P<0.05) in diets with 4.5% oil, regardless of the temperature. These results were similar to Spencer et al (2005), who observed higher fat thickness in animals fed diets containing lower crude protein and higher inclusion level of soybean oil. These results may be related to the higher value of net energy provided by low crude protein diets containing amino acid addition, coupled with the effect of extra caloric oil.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In the present study, effect of crude protein only occurred (P<0.05) in diets with 4.5% oil, regardless of the temperature. These results were similar to Spencer et al (2005), who observed higher fat thickness in animals fed diets containing lower crude protein and higher inclusion level of soybean oil. These results may be related to the higher value of net energy provided by low crude protein diets containing amino acid addition, coupled with the effect of extra caloric oil.…”
Section: Resultssupporting
confidence: 79%
“…In the case of diets with reduced crude protein, this effect cannot be shown due to a greater amount of free amino acids and a lower protein diet, while in the warm environment, the lower feed intake may have limited this effect. Spencer et al (2005) found improvement in feed conversion of animals kept in the heat when receiving diets with 8% of soybean oil. According to the authors, this is due to the lowest caloric increment generated by the oil in the diets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological influence of heat stress is impacted by duration of exposure to extreme temperatures (Renaudeau et al, 2007), night cooling (Xin and DeShazer, 1991;Patience et al, 2005), relative humidity (Huynh et al, 2005), diet composition (Jørgensen et al, 1996;Kerr et al, 2003), and genetics (Brown-Brandl et al, 2001;Sutherland et al, 2006), among others. In particular, ME content (Baldwin and Sainz, 1995;Rodrigues et al, 2012), protein and AA balance (Kerr et al, 2003;Spencer et al, 2005;Wolp et al, 2012), dietary additives (Zier-Rush et al, 2014) ,and mineral concentrations (Haydon et al, 1990;Kim et al, 2009) all affect responses to heat stress. To understand the relationships among variables, a mixed-effect linear model of absolute intake was also derived from the data set.…”
Section: Model Improvementmentioning
confidence: 99%
“…Park et al (2012) noted that dietary fat plays a considerable role in the development of growing-finishing pigs because of its high energy content. Moreover, it is recommended for use in growingfinishing pigs being reared under environmental heat stress due to a lower heat increment than other feedstuff (Spencer et al, 2005). Jung et al (2003) found that the replacement of animal fat with vegetable oil rich in unsaturated fatty acids, such as soybean oil or corn oil, resulted in an improved growth performance in weaning pigs.…”
Section: Introductionmentioning
confidence: 99%